Localizando o pretérito perfecto compuesto na linha do tempo: o estágio da gramaticalização do PPC nas variedades diatópicas argentinas - Araújo, Leandro Silveira de; Berlinck, Rosane de Andrade [UNESP] (My University, 2013)
The aim of this study was to observe Argentine diatopic varieties and to identify in which stage of the evolution of the pretérito perfecto compuesto (PPC) the use of compound tense fits into these variations. Therefore, we assume as assumptions (I) some authors` description of the evolutionary stages of this verb tense in Spanish, (II) the description of the values assigned to the perfecto compuesto in the dialect regions of Argentina and (III) the contributions of studies on grammaticalization for the verb tenses analysis.

O principal objetivo deste trabalho foi observar as variedades diatópicas da Argentina e identificar em que etapa da evolução do pretérito perfecto compuesto (PPC) se encaixa o uso da forma composta nessas variedades. Para tanto, assumimos como pressuposto (I) a descrição que fazem alguns autores das etapas evolutivas dessa forma verbal na língua espanhola; (II) a descrição dos valores atribuídos ao perfecto compuesto nas diferentes regiões do país e (III) as contribuições dos estudos de Gramaticalização para a análise dos tempos verbais.
Finding the pretérito perfecto compuesto in the timeline: the stage of grammaticalization of the PPC in the Argentinian diatopical varieties
Keywords: Pretérito Perfecto Compuesto; Grammaticalization; Argentina; Linguistic Variation and Change; Pretérito Perfecto Compuesto; Gramaticalização; Variação e mudança lingüística; Espanhol argentino